The Ukrainian Catholic University: its development and educational mission today. Issue 1 (2nd January 2020) - Dzhedzhora, Olena
Abstract : The article deals with the revitalisation of Catholic education in Ukraine after the collapse of the Soviet system and the Ukrainian Greek Catholic Church's emergence from the underground. It speaks of the reinstitution and the 25 year work of the Ukrainian Catholic University – the easternmost Catholic university in Europe, and the only Catholic university in the territory of the former Soviet Union. The article provides brief historical information, an analysis of the general crisis, needs and problems of education in present-day Ukraine, and shows how a small academic institution, founded upon the principles of regard for human dignity, faithfulness to the Church, and a sense of social responsibility, can be an agent for positive change in society at large.